Exploring the Impact of the COVID-19 Pandemic on Perceptions of National Scheduled Childhood Vaccines Among Māori and Pacific Caregivers, Whānau, and Healthcare Professionals in Aotearoa New Zealand - Charania, Nadia; Tonumaipe’a, Daysha; Barbarich-Unasa, Te Wai; Iusitini, Leon; Davis, Georgina; Pacheco, Gail; Wilson, Denise (Taylor and Francis, 2024)
In Aotearoa New Zealand, there has been a marked decrease in the uptake of routine childhood vaccinations since the onset of the COVID-19 pandemic, particularly among Māori and Pacific children. This Māori and Pacific-centered research used an interpretive description methodology. We undertook culturally informed interviews and discussions with Māori and Pacific caregivers (n = 24) and healthcare professionals (n = 13) to understand their perceptions of routine childhood vaccines. Data were analyzed using reflexive thematic analysis and privileged respective Māori and Pacific worldviews. Four themes were constructed. “We go with the norm” reflected how social norms, health personnel and institutions promoted (and sometimes coerced) participants’ acceptance of routine vaccines before the pandemic. “Everything became difficult” explains how the pandemic added challenges to the daily struggles of whānau (extended family networks) and healthcare professionals. Participants noted how information sources influenced disease and vaccine perceptions and health behaviors. “It needed to have an ethnic-specific approach” highlighted the inappropriateness of Western-centric strategies that dominated during the initial pandemic response that did not meet the needs of Māori and Pacific communities. Participants advocated for whānau-centric vaccination efforts. “People are now finding their voice” expressed renewed agency among whānau about vaccination following the immense pressure to receive COVID-19 vaccines. The pandemic created an opportune time to support informed parental vaccine decision-making in a manner that enhances the mana (authority, control) of whānau. Māori and Pacific-led vaccination strategies should be embedded in immunization service delivery to improve uptake and immunization experiences for whānau.
Keywords: 1107 Immunology; 1108 Medical Microbiology; 1115 Pharmacology and Pharmaceutical Sciences; Virology; 3204 Immunology; 3206 Medical biotechnology; 3207 Medical microbiology